Computers and the law - Bainbridge, David I. (London : Pitman, 1990)
Offers a discussion of the conjunction between the law and computer technology. It describes the legal implications of acquiring, developing and using computer equipment and software and analyses the impact that computer technology has on law.
Includes bibliographical references and index.
oif 10/09/14
Loan
Keywords: Computers -- Law and legislation -- Great Britain; Great Britain -- Computer systems -- Legal aspects